2023
DOI: 10.1101/2023.02.23.529777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitroandin vivoeffects of zoledronate on senescence and senescence-associated secretory phenotype markers

Abstract: In addition to reducing fracture risk, zoledronate has been found in some studies to decrease mortality in humans and extend lifespan and healthspan in animals. Because senescent cells accumulate with aging and contribute to multiple co-morbidities, the non-skeletal actions of zoledronate could be due to senolytic (killing of senescent cells) or senomorphic (inhibition of the secretion of the senescence-associated secretory phenotype [SASP]) actions. To test this, we first performed in vitro senescence assays … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…BPs can access non-mineralised tissues (7). The extensive range of currently reported non-skeletal effects include extending longevity in mouse models of progeria (8), enhancing human stem cell life span, DNA repair and tissue regeneration (9), effects on tumour growth, prevention of oxidative damage, promotion of autophagy (10), and modulation of cellular senescence (11).…”
Section: Discussionmentioning
confidence: 99%
“…BPs can access non-mineralised tissues (7). The extensive range of currently reported non-skeletal effects include extending longevity in mouse models of progeria (8), enhancing human stem cell life span, DNA repair and tissue regeneration (9), effects on tumour growth, prevention of oxidative damage, promotion of autophagy (10), and modulation of cellular senescence (11).…”
Section: Discussionmentioning
confidence: 99%
“…Significant progress in understanding diseases related to aging has been made over the last few years by identifying senescent cells as common substrate of a plethora of age-related diseases 1,2 termed senopathies 3 . Since the initial discovery of senolytics 4 , research on senescent cell targeting compounds progressed quickly [5][6][7][8][9][10][11][12][13][14] and clinical trials of this new class of drugs are ongoing 15 . This creates a necessity for companion diagnostics of senescence that allow early assessment of safety and efficacy of senolytic drug candidates and the detection of sensitive clinical endpoints 16 .…”
Section: Mainmentioning
confidence: 99%
“…86 In addition to these observed changes in the CV system following bisphosphonate exposure, data have shown that zoledronate can have immunomodulatory effects including reduction in senescence-associated chemokines (such as CCL7, IL-1β, TNFRSF1A, and TGFβ1) and possible impact on immune cell subpopulations. [87][88][89] The role of these changes in the CV system and their impact on CV outcomes remain unclear. In figure 1, we have summarized the cardioprotective benefits of bisphosphonate therapy with a hypothesized mechanism based on the available pre-clinical and clinical data.…”
Section: Bisphosphonatesmentioning
confidence: 99%